The Effects of Reward Systems and Organizational Culture on Job Satisfaction among Civil Servants: Evidence from a Local Government - Muhammad Rizal; Bangun Putra Prasetya (Lembaga Pengembangan Kinerja Dosen, 2025)
Unemployment and increasingly competitive labor market conditions pose significant challenges for public sector organizations in managing and retaining human resources effectively. One critical aspect of human resource management is job satisfaction, which plays a strategic role in influencing employee performance, organizational commitment, and public service quality. This study aims to examine the effects of reward systems and organizational culture on job satisfaction among civil servants in the Bantul Regency Government, Yogyakarta. This research employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to 96 civil servants, selected using purposive sampling based on predefined criteria. The data were analyzed using multiple linear regression, supported by descriptive analysis and classical assumption tests. Hypothesis testing was conducted using partial t-tests, a simultaneous F-test, and the coefficient of determination. The results reveal that reward does not have a significant effect on job satisfaction, indicating that standardized and routine reward systems in the public sector may reduce their motivational impact. In contrast, organizational culture has a positive and significant effect on job satisfaction, suggesting that shared values, norms, and supportive work environments play a dominant role in shaping employee satisfaction. Simultaneously, reward and organizational culture significantly influence job satisfaction, with organizational culture emerging as the most influential variable. These findings highlight the importance of strengthening organizational culture as a strategic approach to enhancing job satisfaction among civil servants. The study contributes to the public sector human resource management literature by providing empirical evidence from a local government context and offers practical insights for policymakers seeking to improve employee well-being and organizational performance.